2015
DOI: 10.3766/jaaa.14053
|View full text |Cite
|
Sign up to set email alerts
|

A Patient-Centered, Provider-Facilitated Approach to the Refinement of Nonlinear Frequency Compression Parameters Based on Subjective Preference Ratings of Amplified Sound Quality

Abstract: By referencing the recommended sensation levels of amplitude compression (e.g., NAL-NL2) in the ear canal of hearing aid wearers, the targeting of NFC parameters can likely be optimized with respect to improvements in effective audibility that may contribute to speech recognition without adversely impacting sound quality. After targeting of NFC parameters, providers can facilitate decisions about the use of NFC parameters (strengths of processing) via sound quality preference judgments using paired comparisons. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Such high values of Sf are unlikely to have a marked effect on sound quality. In the remaining three studies (Parsa et al, 2013 ; Souza et al, 2013 ; Johnson & Light, 2015 ), a range of frequency-compression settings [ Sf = 2, 3, 4 kHz and CR = 2, and Sf = 3 kHz and CR = 6 and 10; Sf = 1.6, 2, 2.5, 3.15 kHz and CR = 2 for Parsa et al ( 2013 ); Sf = 1, 1.5 or 2 kHz and CR = 1.5, 2 or 3 for Souza et al ( 2013 ); and a range of individually chosen settings for Johnson and Light ( 2015 )], as well as a control condition with no frequency compression were used, providing some insights into the effects of frequency-compression settings on sound quality.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Such high values of Sf are unlikely to have a marked effect on sound quality. In the remaining three studies (Parsa et al, 2013 ; Souza et al, 2013 ; Johnson & Light, 2015 ), a range of frequency-compression settings [ Sf = 2, 3, 4 kHz and CR = 2, and Sf = 3 kHz and CR = 6 and 10; Sf = 1.6, 2, 2.5, 3.15 kHz and CR = 2 for Parsa et al ( 2013 ); Sf = 1, 1.5 or 2 kHz and CR = 1.5, 2 or 3 for Souza et al ( 2013 ); and a range of individually chosen settings for Johnson and Light ( 2015 )], as well as a control condition with no frequency compression were used, providing some insights into the effects of frequency-compression settings on sound quality.…”
mentioning
confidence: 99%
“…In three other studies, the effects of frequency compression on both speech and music were addressed (Parsa et al, 2013 ; Brennan et al, 2014 ; Picou et al, 2015 ). The remaining three studies were concerned with the effects of frequency compression on speech only (Souza et al, 2013 ; Johnson & Light, 2015 ; Miller et al, 2016 ). In three studies (Brennan et al, 2014 ; Picou et al, 2015 ; Miller et al, 2016 ), only one setting of frequency compression was used for each participant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of speech perception as it relates to sound quality, across adaptive FL parameters, is something that needs further research. The use of patient-driven listening tasks, such as the paired comparison approach used in the Johnson and Light (2015) study, may help with further exploration of sound quality effect across different FL settings, for a given fitting.…”
Section: Summary and Concluding Discussionmentioning
confidence: 99%
“…Johnson and Light (2015) evaluated the sound quality preferences of adult listeners with severe highfrequency losses, wearing different clinical strengths of NFC compared with conventional hearing aid processing. They found that as the strength of FL was increased, more participants preferred the sound quality of the weaker NFC settings (Johnson and Light, 2015). The authors concluded that modifications to the strength of NFC should be completed in combination with measurements of effective audibility.…”
mentioning
confidence: 99%